Performance Characteristics of Different Anti-Double-Stranded DNA Antibody Assays in the Monitoring of Systemic Lupus Erythematosus. (31st December 2017) - Mahler, Michael; Bentow, Chelsea; O'Malley, Tyler; Ibarra, Claudia; Conklin, John; Aure, Mary Ann R.; Dervieux, Thierry
Abstract : Objective . We sought to evaluate different anti-double-stranded DNA assays for their performance characteristics in monitoring disease activity fluctuations in systemic lupus erythematosus (SLE). Methods . 36 active SLE patients were followed monthly. At each study visit (total n = 371 ), blood was collected and disease activity was scored using the SELENA-SLEDAI (excluding anti-dsDNA or complement components) and by a physician's global assessment (PGA). Four anti-dsDNA tests were compared. Linear mixed-effects models with random intercept and fixed slopes were used to evaluate the relationship between the longitudinal fluctuations of disease activity and anti-dsDNA titers. Results . At enrollment, positivity for QUANTA Lite and high-avidity anti-dsDNA assay was both 64% and significantly lower than anti-dsDNA positivity by QUANTA Flash (83%) and CLIFT (96%). Linear mixed-effects modeling indicated that the change in clinical SELENA-SLEDAI scores was associated with the titers of all anti-dsDNA with QUANTA Flash yielding the highest marginal R 2 (0.15; p < 0.01 ). QUANTA Flash was the only anti-dsDNA assay significantly associated with the change in PGA (marginal R 2 = 0.05 ; p < 0.01 ). Conclusion . These data indicate that anti-dsDNA antibodies determined by QUANTA Flash have a value in monitoring SLE disease activity.